STRATEGI PENGEMBANGAN AGROWISATA KAMPUNG MARKISA BLUNYAHREJO KELURAHAN KARANGWARU KECAMATAN TEGALREJO KOTA YOGYAKARTA - A Rofiqi Wahyudi; Rini Raharti (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
The Blunyahrejo Markisa Agrotourism Village, located in Waru Village, Tegalrejo District, Yogyakarta City, has the potential to be developed as a tourist area. The development of this region is focused on strengthening local attractions through community empowerment, utilizing natural potential, as well as promoting tourism and the creative economy. The main programs include skills training for residents, development of superior products from passion fruit, and assistance in diversifying processed passion fruit products. In addition, collaboration with the government, private sector and universities is expected to accelerate infrastructure development and increase human resource capacity. With a participatory and sustainable approach, the Blunyahrejo Markisa Agrotourism Village is expected to become a successful example of thematic village development that supports the local economy while protecting the natural environment.